Recombinant biosynthesis of bacterial cellulose in genetically modified Escherichia coli - BULDUM, GİZEM (SPRINGER, 2018)
Bacterial cellulose (BC) exhibits unique properties such as high purity compared to plant-based cellulose; however, commercial production of BC has remained a challenge, primarily due to the strain properties of cellulose-producing bacteria. Herein, we developed a functional and stable BC production system in genetically modified (GM) Escherichia coli by recombinant expression of both the BC synthase operon (bcsABCD) and the upstream operon (cmcax, ccpAx). BC production was achieved in GM HMS174 (DE3) and in GM C41 (DE3) by optimization of the culture temperature (22 degrees C, 30 degrees C, and 37 degrees C) and IPTG concentration. BC biosynthesis was detected much earlier in GM C41 (DE3) cultures (3 h after IPTG induction) than those of Gluconacetobacter hansenii. GM HMS174 (DE3) produced dense fibres having a length of approximately 1000-3000 mu m and a diameter of 10-20 mu m, which were remarkably larger than the fibres of BC typically produced by G. hansenii.
Keywords: Bacterial cellulose; Escherichia coli; Recombinant biosynthesis; Optimization of culture conditions; Plasmid maintenance; ACETOBACTER-XYLINUM BRC5; MEMBRANE-PROTEINS; MICROBIAL CELLULOSE; SALMONELLA-TYPHIMURIUM; GENE-EXPRESSION; SYNTHASE; PLASMID; OVEREXPRESSION; CLONING; OPERON